Exercice et apprentissage du métier d'infirmier : à la recherche du Care - Isabelle Eyland; Alain Jean
The notion to take care has always been attached to the function of the nurse but the term of care became more and more popular in diverse domains ad the education, the sociology or the politics. The first mention in the concept date 1970s in the USA and followed up numerous works, written and definitions... In the field of nursing, any situation is the opportunity of a social meeting which allows the nursing, the caregivers exchanges, the emotional commitment and the application activities bound to the care. Nevertheless, the concept is damaged... And what place is it given to it in training for nursing students ?